Estudos Taxonômicos, Filogenéticos e Biossistemáticos em Mansoa DC. (Bignonieae - Bignoniaceae) - Castro, Milene Maria da Silva (2010)
Bignoniaceae is a Pantropical family, but with greater diversification in the Neotropics, its currently consists of 827 species in 82 genera. Mansoa DC. includes 12 species, and Neotropical distribution from central-southern Mexico to northern Argentina, Paraguay, and Bolivia. Previous studies reported the difficulty for circumscribing genus and establish species limits. In order to define the genus and revise the species boundaries it was carried on studies with diferente approaches. Biosystematics studies with molecular ISSR markers, palynological studies, phylogenetic analysis based on nuclear ITS nuclear and plastidial trnL-F, and taxonomic revision. The genus was supported as monophyletic Mansoa based on analyses of ITS and combined of trnL-F and ITS. A complete taxonomic revision is presented with an identification key, descriptions, illustrations, distribution maps, comments and ecological observations of the species, six new taxa are described (five species and one hybrid), and one new combination, one lectotype, one neotype and subdivision of Mansoa into sections based on morphological, phylogenetic studies are presented.